Flexible Working Space for Generation Z Employees in the Banking Sector - Via Lailatur Rizki; Imam Abrori; Masyhuri Masyhuri; Fauzan Muttaqien (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of Flexible Working Space (FWS) and Organizational Support on Employee Performance with Work Life Balance (WLB) as a mediating variable among Generation Z employees in the banking sector in Lumajang City. The research approach uses a quantitative method with primary data collection through a Likert scale-based questionnaire. The research sample consisted of 98 respondents selected using purposive sampling. Data analysis was performed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the help of SmartPLS 4.0 software. The results showed that FWS did not have a significant effect on WLB or employee performance. Conversely, organizational support had a positive and significant effect on WLB and employee performance. In addition, WLB was found to have a significant effect on employee performance and mediated the relationship between organizational support and employee performance, but did not mediate the relationship between FWS and employee performance. These findings confirm that in the context of the regional banking sector, organizational support plays a more strategic role than workplace flexibility in improving work-life balance and the performance of Generation Z employees.